Effect of Mass Flow Rate in a Shell and Tube Heat Exchanger of Different Inner Tube Geometries during Solidification of Phase Change Material - Abdulrazzaq M. Saleh Aljumaily; Akeel A. Mohammed; Sattar J. Aljabair (Diyala Journal of Engineering Sciences, 2024)
The current work consists of a theoretical and experimental investigation of the impact of mass flow rate on the solidification process of phase change materials (PCM) for various inner tube geometries of heat exchangers. The heat exchanger consists of an outer shell filled with paraffin wax as a PCM. Simultaneously, three tested inner tube shapes with the same cross-sectional area are circular, elliptical with minor axis bending, and elliptical with major axis bending. Water was used as the heat transfer fluid (HTF) at two and four L/min flow rates inside the inner tube. A three-dimensional ANSYS simulation was constructed to examine the thermal behaviour of heat exchangers incorporating PCM. The findings demonstrated that when the mass flow rate of HTF decreased, so the solidification time increased. Furthermore, compared to other tube forms, circular tubes offer longer-lasting heat absorption from phase shift materials through the heat transfer fluid. Also, the results show that the heat transfer process between PCM and HTF is controlled by natural convection. solidification begins near the inner tube and then moves towards the casing (horizontal axis at 0°, then inclined axis at 45°, followed by the vertical axis at 90°). Moreover, it was observed that the maximum theoretical and experimental thermal efficiencies recorded were (67.7%, 71.6%,) for the circular inner tube followed by (49.2%, 53.2%) for the elliptical inner tube with minor axis bending and (44.6%, 48.1%) for the elliptical inner tube with major axis bending at a water volumetric flow rate of 2 L/min, respectively.